Constraints on volcanism, igneous intrusion and stretching on the Rockall-Faroe continental margin - White, R. S.; Eccles, J. D.; Roberts, A. W. (Geological Society, London, Petroleum Geology Conference series, 2011)
The northern North Atlantic margins are classic examples of ‘volcanic’ rifted continental margins, where breakup was accompanied by massive volcanism. We discuss strategies used to obtain good intra- and sub-basalt seismic penetration so as to map the structure and the extruded and intruded igneous volume. We recorded deep penetration reflection data using a 12 000 m long single sensor (Q-)streamer and wide-angle seismic profiles with 85 4-component ocean bottom seismometers, along two transects across the Faroe and Hatton Bank continental margins in the NE Atlantic. Tomographic inversion of both compressional (P) and shear (S) wave crustal velocities are crucial in improving the reflection image and in constraining the nature of the sub-basalt lithology and the volume of extruded and intruded melt. Beneath the basalts, which reach 5 km thickness, is a low-velocity zone with P- and S-wave velocities characteristic of sedimentary rocks intruded by basalt sills. The underlying stretched continental basement contains abundant intrusive igneous sills on the rifted margin. Near the Faroe Islands, for every 1 km along-strike, 340–420 km3 of basalt was extruded, while 560–780 km3 was intruded into the continent–ocean transition (COT). Lower-crustal intrusions are focussed mainly into a narrow zone less than 50 km wide on the COT, whereas extruded basalts flow >100 km from the rift. Melt on the COT is intruded into the lower crust as sills which cross-cut the stretched and tilted continental fabric, rather than as ‘underplate’ of 100% melt, as has often been assumed previously. Our igneous thickness and velocity observations are consistent with the dominant control on the melt production being rifting above mantle with a temperature elevated above normal. The mantle temperature anomaly was up to 150°C above normal at the time of continental breakup, decreasing by c. 70–80°C over the first 10 Ma of seafloor spreading.